1953
DOI: 10.1136/jcp.6.3.232
|View full text |Cite
|
Sign up to set email alerts
|

A Fertility Index Derived from Semen Analysis

Abstract: The study of human semen and its importance in assessing the probable fertility of a given marriage has received a great deal of attention in recent years. Unlike blood or urea estimations, semen analysis has no fixed standards of normality. Harvey and Jackson (1945) and Hammen (1944) showed that the criteria of fertility given by earlier workers (Moench and Holt, 1931 ;Hotchkiss, 1936;Lane Roberts, Sharman, Walker, and Wiesner, 1939;Weisman, 1941) were set far too high. More recent work (Falk and Kaufman, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1957
1957
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The method described in Harvey's report [2] was partially modified [3]. FI was calculated as follows: FI = sperm density (910 6 /ml) 9 sperm motility (%) 9 normal sperm morphology rate (%/10,000).…”
Section: Fertility Index (Fi)mentioning
confidence: 99%
“…The method described in Harvey's report [2] was partially modified [3]. FI was calculated as follows: FI = sperm density (910 6 /ml) 9 sperm motility (%) 9 normal sperm morphology rate (%/10,000).…”
Section: Fertility Index (Fi)mentioning
confidence: 99%
“…However there is a study that did not show a significant difference in ST levels between healthy subjects and those with seminal quality alterations (18). There was a statistically significant correlation (Table 2) between ST and all ele- The FI is a general index to evaluate the semen quality, which was better than any single semen parameter (2). In the present study we found a FI significantly lower in the case group than in the control group (Table 1) the regulation of testicular function (steroidogenesis and spermatogenesis) during pathophysiological states as well as under normal physiological conditions (20).…”
Section: Discussionmentioning
confidence: 99%
“…The HP identified in HD patients is often characterized by elevated serum levels of FSH, LH, and PRL, as well as low testosterone b Fertility index (FI) = sperm density (0.10 6 mL -1 ) × sperm motility × sperm morphology (this value represents the number of sperm with forward motile and normal morphology in each mL), as described by Harvey (1953). patients caused by blockages at one or more sites along the hypothalamic-pituitary-testicular (HPT) axis (12,13).…”
Section: Discussionmentioning
confidence: 99%